Phosphorylation-deficient G-protein-biased μ-opioid receptors improve analgesia and diminish tolerance but worsen opioid side effects - A. Kliewer (Nature Portfolio, 2019)
Tolerance and other side effects are important limitations to the use of opioids as analgesics. In this study, the authors generated mice lacking phosphorylation sites on the µ-opioid receptor to assess their contribution to the analgesic, tolerance and side effect profile of opioid analgesics.